Pemberdayaan Ekonomi Umat Buddha melalui Pengembangan Perkebunan Durian Berkelanjutan dan Pengelolaan Hasil Pasca Panen di Kabupaten Wonogiri - Mujiyanto Mujiyanto; Sukarti Sukarti; Arina Afiyati Shadikah; Adi Nugroho Susanto Putro (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This Community Service (PkM) activity aims to improve the economic welfare of the Buddhist community in Karang Village, Wonogiri Regency, by optimizing the potential of durian farming. The main problems faced by partners were traditional cultivation methods, low market value due to limited post-harvest processing, and lack of farm management. The implementation method utilized a community empowerment approach, which included socialization, technical training on sustainable cultivation, mentoring in processed product development (dodol and jam), and strengthening economic institutions based on Buddhist values. The results of the activity showed an increase in the technical capacity of farmers in selecting superior seeds and organic fertilization, as well as the creation of processed durian products with higher economic value. The integration of agribusiness skills and the principle of Sammā Ājīva (Right Livelihood) is proven to be able to transform farmers’ mindsets from subsistence to independent, productive, and environmentally conscious. This program provides a model for religious community economic empowerment that is in harmony with ecological sustainability.